Self-Regulated learning with the use of portfolio: analysis of student perceptions - Medeiros, Marlene (2020)
This article investigates perceptions of masters and doctorates students in Administration regarding the use of the portfolio as a self-regulated learning tool. The model of Pintrich (2000), which comprises as cognitive, motivational, behavioral and context areas, was used as theoretical basis for the content of these perceptions, particularly as the reaction and reflection phase. In the data collection, participative observation and documents, obtained from the self-assessments of the students. Data were analyzed by the content analysis and clustering. The results showed that the methodology employed enhanced learning, making the discourses more active and self - critical. Four clusters were identified that portrayed students' perceptions of learning and adaptability to the methodological proposal of self-regulation: immediate adopters, adaptive majority, cautious and resistant. It was possible to identify the positive and negative axes related to the adaptability to the use of the portfolio. The study corroborates the idea of feasibility and effectiveness of the portfolio tool as an alternative methodology to the traditional teaching and learning evaluation model.